2008
DOI: 10.1086/592139
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta, Dust, and Synchrotron Radiation in SNR B0540−69.3: A More Crab‐Like Remnant than the Crab

Abstract: We present near and mid-infrared observations of the pulsar-wind nebula (PWN) B0540-69.3 and its associated supernova remnant made with the Spitzer Space Telescope. We report detections of the PWN with all four IRAC bands, the 24 µm band of MIPS, and the Infrared Spectrograph (IRS). We find no evidence of IR emission from the X-ray/radio shell surrounding the PWN resulting from the forward shock of the supernova blast wave. The flux of the PWN itself is dominated by synchrotron emission at shorter (IRAC) wavel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
159
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(186 citation statements)
references
References 67 publications
25
159
2
Order By: Relevance
“…Moreover, our nIR and the optical fluxes were corrected for the contribution from the pulsar and the background/foreground stars overlapping the PWN, while this is clearly not the case for the Spitzer fluxes, where both the pulsar and the stars are not resolved at the angular scale of the IRAC and MIPS data. For this reason, the true intrinsic nebular fluxes in the mIR are, most likely, lower that those presented in Williams et al (2008). We note that the PWN spectral index has to change once more somewhere between the nIR/mIR and the radio bands from α PWN nIR = 0.56 to α PWN R = 0.25 ± 0.1 (Manchester et al 1993).…”
Section: The Pwn Multi-wavelength Spectrummentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, our nIR and the optical fluxes were corrected for the contribution from the pulsar and the background/foreground stars overlapping the PWN, while this is clearly not the case for the Spitzer fluxes, where both the pulsar and the stars are not resolved at the angular scale of the IRAC and MIPS data. For this reason, the true intrinsic nebular fluxes in the mIR are, most likely, lower that those presented in Williams et al (2008). We note that the PWN spectral index has to change once more somewhere between the nIR/mIR and the radio bands from α PWN nIR = 0.56 to α PWN R = 0.25 ± 0.1 (Manchester et al 1993).…”
Section: The Pwn Multi-wavelength Spectrummentioning
confidence: 66%
“…This is probably due to the 336W flux, which is lower than the best-fit optical/nIR PL and, then, produces a steepening of the PL in the optical. The best-fit Chandra PL spectrum of the PWN in 0.6-10 keV energy range Kaaret et al (2001) is also shown in Fig.8, together with the mIR fluxes from the Spitzer IRAC and MIPS observations (Williams et al 2008) and the radio fluxes from Manchester et al (1993). The extrapolation of the PWN X-ray spectrum, with spectral index α PWN X = 1.04, to the nIR-optical domain clearly overestimates the PWN optical and nIR fluxes.…”
Section: The Pwn Multi-wavelength Spectrummentioning
confidence: 85%
See 1 more Smart Citation
“…A sharp, probably double-knee break between the optical and X-rays is visible in the spectrum of the similar age 3C 58 PWN 6 . The spectrum of B0540-69, which is slightly older than the Crab, suggesting a break at a few microns (Mignani et al 2012), and then flattens again at longer wavelengths (Williams et al 2008). A double-knee break between the optical and X-rays is not excluded either (Serafimovich et al 2005).…”
Section: Multiwavelength Spectrum Of the Torus-like Pwnmentioning
confidence: 85%
“…A double-knee break between the optical and X-rays is not excluded either (Serafimovich et al 2005). At the same time, the IR part of the G21.5-09 spectrum is probably almost 3 The data are taken for the Crab from Green et al (2004), Temim et al (2006), Grasdalen (1979), Veron-Cetty & Woltjer (1993), and Kirsch et al (2005); for G21.5-0.9 from Zajczyk et al (2012); for B0540-69.3 from Manchester et al (1993), Williams et al (2008), Mignani et al (2012), and Serafimovich et al (2005); for 3C 58 from Shibanov et al (2008), Shearer & Neustroev (2008), and Slane et al (2008). 4 We indicate in the plot the SNR (870 yr, Bietenholz & Bartel 2008) and spindown (4800 yr, Camilo et al 2006) ages for this PWN.…”
Section: Multiwavelength Spectrum Of the Torus-like Pwnmentioning
confidence: 99%